Tracing Life. Notes on Ikebana política[Political Ikebana] by Claudia del Río - Giordano, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper attempts a critical reading of Ikebana política , the book edition of a series of fragments ex - tracted from the diaries and personal notebooks of the Argentinian artist Claudia del Río. We focus on two topics: a) ethical and aesthetic similarities between the composition of rhapsodic books using the collage technique and the montage of a drawing exhibition, and b) the ways in which the publication of personal writing responds -through the fragmentation and dispersion of egotistical traits- to the modern imperative of transforming one’s life into a work of art. This paper also explores the ethical scope of self writing when read as a series of spiritual exercises, as well as the relation between the archival impulse pushes forth the composition of Ikebana política, and the self figuration of the author as artist and self- taught teacher.